2019
DOI: 10.1108/ijis-12-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Team-member exchange and innovative work behaviour

Abstract: Purpose In the context of team's influence on its members, this paper aims to investigate the effects of team-member exchange (TMX) on members' innovative work behaviour (IWB). The current study presents a moderated mediation model and examines the mechanisms and conditions involved in TMX-IWB relationship. Design/methodology/approach A quantitative research methodology was adopted where 156 engineering and management students (grouped into 33 teams) were given a task in the form of an assignment to be compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 75 publications
(94 reference statements)
3
20
0
1
Order By: Relevance
“…The findings suggest that the relationship between PE and IPD is significant, and thus academics who feel psychologically empowered express this through IPD. This finding aligns with the work of Singh and Sarkar (2019) and Ghosh et al (2019), where structural empowerment and PE, respectively, were found to influence innovative service delivery. However, the result is at variance with the results reported by Asag-Gau and Van Dierendonck (2011) and Wong Humborstad and Perry (2011) on the predictive role of PE on work outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…The findings suggest that the relationship between PE and IPD is significant, and thus academics who feel psychologically empowered express this through IPD. This finding aligns with the work of Singh and Sarkar (2019) and Ghosh et al (2019), where structural empowerment and PE, respectively, were found to influence innovative service delivery. However, the result is at variance with the results reported by Asag-Gau and Van Dierendonck (2011) and Wong Humborstad and Perry (2011) on the predictive role of PE on work outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, most papers on IWB are published either in innovation-specific journals, psychology or sustainability journals, and the European Journal of Innovation Management leads the portfolio. Concerning the study design, majority of the researchers have used structural equation modeling for data analysis (Afsar et al , 2021; Ghosh et al , 2019; Grošelj et al , 2021). The coauthorship analysis has shown that the IWB research is scattered across nations, and interesting trend to note is that authors from developing nations are frequently collaborating with authors from the developed world.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, adopting new methods for creating new products and services is what we mean when talking about innovation. To survive global competition and uncertain business environment, modern organizations are required to constantly make innovations (Ghosh et al , 2019). In this rapidly changing environment, employees’ IWB is considered a foundation among the numerous types and degrees of innovation because it is the individuals that develop the ideas (Masood and Afsar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor pada level organisasi di antaranya, praktik sumber daya manusia (Ma Prieto & Pilar Pérez-Santana, 2014), iklim organisasi (Basu, 2017, dan tuntutan pekerjaan (Dediu, Leka, & Jain, 2018). Pada level kelompok di antaranya, pertukaran anggota kelompok (Ghosh, Bharadwaja, Yadav, & Kabra, 2019), pertukaran pemimpin-anggota (Saeed, Afsar, Cheema, & Javed, 2019), dan gaya kepemimpinan (Khan, Aslam, & Riaz, 2012). Faktor dari level individu seperti keterikatan kerja (Jason & Geetha, 2019;Park, Song, Yoon, & Kim, 2014), kepercayaan (Agarwal, 2014;Kim & Park, 2017), dan creative self-efficacy (Afsar & Masood, 2018;Li, Liu, Liu, & Wang, 2017).…”
Section: Pendahuluanunclassified